Sufism Thoughts of al-Qushayrī and It’s Relevance to Contemporary Muslim Societies - Pangulu Abdul Karim (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
Al-Qushayrī is one of the leading imams in the Sunni Sufism tradition. Mystical thinking within the integration framework between the shariah and haqiqah (al-jam‘ bayna al-sharī’ah wa al-haqiqah) instrumental in eroding the tension between the shariah and nature. In addition, al-Qushayrī’s thought of Sufism is moderate and balanced. So, it is appropriate to avoid extremes in religion. Thus, the sufism thought of al-Qushayrī is relevant for contemporary humans, especially Muslims societies, to balance advances in technology and science and material with the development of the spiritual dimension.